The Parvalbumin Hypothesis of Autism Spectrum Disorder - Filice, Federica; Janickova, Lucia; Henzi, Thomas; Bilella, Alessandro; Schwaller, Beat (Frontiers in Cellular Neuroscience, 2020)
The prevalence of autism spectrum disorder (ASD)—a type of neurodevelopmental disorder—is increasing, and is around 2% in North America, Asia, and Europe. Besides the known genetic link, environmental, epigenetic, and metabolic factors have been implicated in ASD etiology. Although highly heterogeneous at the behavioral level, ASD comprises a set of core symptoms including impaired communication and social interaction skills as well as stereotyped and repetitive behaviors. This has led to the suggestion that a large part of the ASD phenotype is caused by changes in a few and common set of signaling pathways, the identification of which is a fundamental aim of autism research. Using advanced bioinformatics tools and the abundantly available genetic data, it is possible to classify the large number of ASD-associated genes according to cellular function and pathways. Cellular processes known to be impaired in ASD include gene regulation, synaptic transmission affecting the excitation/inhibition balance, neuronal Ca2+ signaling, development of short-/long-range connectivity (circuits and networks), and mitochondrial function. Such alterations often occur during early postnatal neurodevelopment. Among the neurons most affected in ASD as well as in schizophrenia are those expressing the Ca2+-binding protein parvalbumin (PV). These mainly inhibitory interneurons present in many different brain regions in humans and rodents are characterized by rapid, nonadaptive firing and have a high energy requirement. PV expression is often reduced at both mRNA and protein levels in human ASD brain samples and mouse ASD (and schizophrenia) models. Although the human PVALB gene is not a high-ranking susceptibility/risk gene for either disorder and is currently only listed in the SFARI Gene Archive, we propose and present supporting evidence for the Parvalbumin Hypothesis, which posits that decreased PV level is causally related to the etiology of ASD (and possibly schizophrenia).